Culvitation of Maggot (Black Soldier Fly) in the Organic Waste Processing at Selopuro Landfills (TPA): Budidaya Maggot (Black Soldier Fly) dalam Pengolahan Sampah Organik di Tempat Pemrosesan Akhir (TPA) Selopuro - Chandra Nabila Rahmawati; Firra Rosariawari; Anik Krisnawati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Waste is the remaining material from human activities that is no longer needed. Waste must go through a good handling process so that it does not cause problems for the environment. Organic waste can provide benefits if managed properly. Organic waste processing requires appropriate technology so that no new waste is generated from the processed results. One of these technologies uses the maggot cultivation method carried out at the Selopuro TPA (Final Processing Place). After the maggots grow large due to the process of decomposing organic waste, maggots can be used as the main feed in catfish cultivation which is also found at the Selopuro TPA. The purpose of this activity is to analyze the effectiveness of the maggot cultivation method in reducing organic waste at the Selopuro TPA. The implementation method is by direct observation. The data used in this study is primary data. The results of the study show that managing organic waste using maggots is an environmentally friendly and inexpensive processing alternative, and is able to decompose organic waste faster.